Histological characteristics of diffuse idiopathic skeletal hyperostosis. Issue 1 (29th April 2016) - Kuperus, Jonneke S.; Westerveld, L. Anneloes; Rutges, Joost P. H. J.; Alblas, Jacqueline; van Rijen, Mattie H. P.; Bleys, Ronald L. A. W.; Öner, F. Cumhur; Verlaan, Jorrit‐Jan
ABSTRACT: Diffuse idiopathic skeletal hyperostosis (DISH) is a predominantly radiographic diagnosis and histological knowledge of DISH is limited. The aim of this study was to describe the histological characteristics of DISH in the spinal column and to study the relation between DISH and intervertebral disc (IVD) degeneration. Therefore, 10 human cadaveric spines with fluoroscopic evidence of DISH were compared with 10 controls. Plain radiographs and computed tomography (CT) scans were obtained and tissue blocks were resected from three predefined levels of all specimens. The microscopic sections were scored by two blinded observers using a newly developed scoring system specific for characteristics of DISH and a validated scoring system for IVD degeneration. Maximum IVD height was measured on the CT scans. Analyses were performed using Fisher's exact test and Student's t ‐test. When compared to controls, the right sided sections from DISH specimens showed partial or complete bone bridges, consisting of cortical woven bone, accompanied by morphological changes in the adjoining part of the IVD. Using the histological scoring system for DISH, all parameters were significantly different between the DISH and control group ( p  < 0.01). The contralateral location did not show differences between the groups. The overall degree of IVD degeneration and height of IVD was comparable for the two groups. The histopathological changes observed in spines with DISH corresponded to the fluoroscopic images and CT scans. The degree of IVD degeneration and IVD height was comparable for both groups, suggesting a limited role for IVD degeneration in the pathogenesis of DISH. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:140–146, 2017.